Thinking Styles and Cognitive Creativity in Iranian Female Adolescents: The Mediating Role of Optimism - A Structural Equation Modeling Study - Zahra Saedi; Elham Taheri; Mehdi Amiri (Universitas Pendidikan Ganesha, 2025)
This Adolescents’ cognitive creativity plays a crucial role in their academic success, psychological well-being, and adaptive functioning in an increasingly complex world. However, many students experience difficulties in developing creativity due to limited adaptive thinking patterns and low levels of optimism, which may constrain their cognitive flexibility and problem-solving capacities. This study aimed to analyze the relationships between thinking styles, optimism, and cognitive creativity, as well as to examine the mediating role of optimism in the relationship between thinking styles and creativity. Employing a cross-sectional correlational design grounded in Sternberg’s theory, this research involved 350 eleventh-grade female students selected through multistage cluster sampling. Data were collected using standardized instruments, including the Thinking Styles Inventory, the Cognitive Creativity Scale, and the Life Orientation Test. Structural equation modeling with bias-corrected bootstrapping was applied to test direct and indirect effects. The findings revealed that legislative, executive, and judicial thinking styles significantly predicted cognitive creativity both directly and indirectly. Optimism functioned as a significant mediator, strengthening the influence of thinking styles on creativity. The model demonstrated strong explanatory power for both creativity and optimism. In conclusion, adaptive thinking styles and optimism are essential determinants of adolescents’ cognitive creativity. These results imply that educational interventions should be systematically designed to cultivate constructive thinking patterns and foster optimism to enhance students’ creative potential and psychological resilience.